AN ANALYSIS OF FILLERS USAGE IN ACADEMIC PRESENTATION - Stevani, Ana; Sudarsono, Sudarsono; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Ana Stevani, Sudarsono, Iwan SupardiEnglish Language Education Study Program, FKIP Untan PontianakEmail: stevybarajaki@gmail.com